The Countryside from Rurality to Rurbanity - Drozg, Vladimir (Podeželje, 2026)
In the first part of the paper the relations between countryside and town are described. This has changed from self-sufficient countryside over the era of countryside urbanization to the final era of rurbanity. Until the 18th century the countryside and the town were more or less separate, autarchy was the main characteristic of both areas. In the second era, that coincides with industrialization and urbanization process, the city overcomes the countryside. In the third era the strengthening of countryside economic and cultural power can be recognized. In the second part of the article the characteristics of the countryside are presented according to Lefebvre's scheme of production of space. The human activities in space, ideas about the countryside and perception of countryside are the main topics. Among human activities, the changes in settlement structure are presented, the technical and social infrastructure and land use as well. The ideas of countryside have changed from organic structure with tide connections to nature over left behind area that needs the state’s help to new rurality. In the perception of countryside three stages can be recognized: imaginations of rurality, less development area and stage of polyfunctional, hybrid countryside.